HLA-DQ rather than HLA-DR region might be involved in dominant nonsusceptibility to diabetes. - Sterkers, G (1988)
Since HLA-DRw15 (a subdivision of the HLA-DR2 specificity previously called DR2 long) is associated with dominant nonsusceptibility to insulin-dependent diabetes mellitus (IDDM), while HLA-DRw16 (another subdivision of HLA-DR2, previously called DR2 short) is positively associated with the disease, we looked for particular characteristics of HLA products encoded by the DR2 haplotypes of IDDM patients. The results show the following: (i) HLA-DQ molecules of HLA-DRw15-positive IDDM patients are different from those of HLA-DRw15-positive controls, suggesting that the HLA-DQ gene of DRw15 haplotypes is involved in a protective effect. (ii) HLA-DR and -DQ products of DRw16-positive IDDM are functionally indistinguishable from those of HLA-DRw16-positive controls. Furthermore, our data provide evidence that the residue at position 57 on the DQ beta chain could play a crucial biological role in antigen presentation to T cells as far as the DRw16 haplotype is concerned. This observation fits with the recent observation of correlation between DQ beta allelic polymorphism at position 57 and both susceptibility and resistance to IDDM.